Scaling Agile with Jira Align​ A Practical Guide to Strategically Scaling Agile Across Teams, Programs, and Portfolios in Enterprises. - MacNeil, Dean (Packt Publishing, Limited, 2020)
Scaling Agile with Jira Align is a practical guide for agile enterprise planning, delivery, reporting, and forecasting. This book will take you through best practices and use cases with a focus on scaling agile team execution in Jira Software. You'll achieve enterprise-wide agility and value delivery by implementing various features of Jira Align.